eBay PowerUser’s bible - Holden, Greg. (Wiley Pub., Inc., 2007)
Now you can join the millions of eBay users who earn some or all of their income from eBay, with the in-depth instruction you'll find in this comprehensive guide. The basics are all here—how to register, set up a PayPal account, create compelling listings, track income and expenses, report taxes—plus loads of ideas and strategies to help you grow your business and get profitable. Packed with illustrated instructions, valuable tips, and terrific techniques, this is the book you need to move from shopper to eBay PowerUser—and succeed.